The role of small and medium-sized enterprises in development: What can be learned from the German experience? - Hansjörg Herr; Zeynep Mualla Nettekoven (International Labour Organization (ILO), 2018)
Small and medium-sized enterprises (SMEs) play an important role for development. Of importance are Schumpeterian SMEs, which include start-ups that trigger innovation, boost productivity and bring about structural change. Normal SMEs, which only adjust to market pressure, are also important for development and employment. Germany is a role model for SMEs. This is due to several important factors: Germany's local banking system, which is not profit oriented (made up of Sparkassen, or savings banks); the dual vocational system, with its combination of practical and theoretical education; the high social capital of strong employers' associations and trade unions; government support of SME clusters and a big, government-owned development bank (the KfW). SMEs in developing countries typically suffer from limited access to long-term and affordable finance, insufficient institutions for developing a skilled class of entrepreneurs and workers, a low income, and poor policies to support economic and social upgrading of SMEs. Economic upgrading in developing countries is necessary, but it will not be successful without social upgrading. Germany - with its high social capital within the framework of a social market economy, its financial and education system, and its government support for SMEs - can stimulate debates about SMEs in developing countries.
Keywords: 330